Assessment of Heritage Preservation Projects in The Old City of Damascus from The Perspective of International Conventions and Standards - Ramadan, Najia Taher; Jamhawi, Monther; Maksoud, Aref (Al-Adab Journal, 2022)
The Old City of Damascus is distinguished by its many souks, ancient neighborhoods, mosques, churches, khans, and cobbled streets. Although the state has implemented many projects to preserve the cultural heritage in Old Damascus, no study has been conducted to assess the extent to which these projects comply with the directives of cultural heritage charters and standards. Therefore, this research came as a master's thesis to discuss some urban heritage preservation projects in the old city of Damascus and evaluate them from the perspective of international charters and standards, to know the problems resulting from the methods and methodologies used in the preservation process, and to provide an information database on evaluating the conservation methods used in Old Damascus. A group of projects was selected, like, Ancient Damascus without Cars, Medhat Pasha market restoration, Beit Nizam (Nizam House), Beit Kuwatli, and Beit Sibai, after evaluation according to the criteria, the study reached several results, the most important of which is the need to preserve the relationship between Old Damascus within the walls and its surroundings. The research recommends the necessity of linking the directorates responsible for Old Damascus and developing a comprehensive and integrated revival plan based on international standards.